The Officer Compliance of Interlocutory Decisions of The Administrative Court (The Study of Golkar Party and Persatuan Pembangunan Party) - Ahmad Gelora Mahardika (Universitas Serang Raya, 2020)
This study aims to examine and find out how to determine the postponement of the State Administrative Court related to Political Parties, as well as to evaluate the Government's compliance with the Court's Decision even though the decision was in the form of a decision. The focus of this research is related to the government's attitude towards the determination of the delay issued by the Jakarta Administrative Court to the Decree of the Minister of Law and Human Rights related to the management of the United Development Party and the Golkar Party. The research method in this article is normative juridical using the legislative approach and looking at case studies in the United Development Party and the Golkar Party. The conclusion in this article is that the adjournment of the administrative court adjournment is not effective, especially those related to internal political party disputes.